CHALLENGES FACED SMALLSCALE COOPERATIVE POULTRY EGG FARMERS IN IWO ZONE OF OSUN STATE, NIGERIA - Adesina, Shittu K.; Gabriel, Friday Nweke; Jimoh, Bashiru Oladayo; Moore, Nwamaka Chinyere (FUDMA Journal of Sciences, 2025)
This research analyzed challenges encountered by cooperative small scale poultry egg farmers in Iwo Zone of Osun State, Nigeria. Data were collected through the use of a well structured questionnaire for interviews from One hundred and five (105) poultry egg farmers using two-stage sampling techniques. Both descriptive and inferential statistics were utilized to analyze the data obtained. The results of the descriptive statistics analysis revealed that 71.4% of poultry egg farmers had an average age of 46.5 years, indicating that they are within their economically productive age bracket. Moreover, 81.9% of poultry business operators were males, the majority of whom had received formal education, with an average household size of 5 members. The findings also revealed that majority of farmers sourced funds through personal savings. The results of linear regression showed that coefficient associated with feed cost is negative and statistically significant at 1% level. This indicated inverse relationship between feed expenditure and profitability aligns, implying that as cost of feed per bird escalates, the prospective profit diminishes. The main challenges impeding farmers’ profitability included inadequate funds, high feed costs, and marketing complexities, among others. Poultry farmers should strive to alleviate the exorbitant cost of feed, by exploring the use of locally compounded feeds for rearing poultry birds and reducing overall production costs. The government should provide support to farmers to alleviate the constraints faced by poultry farmers, thereby enhancing profitability and raising farmers’ income and standards of living.